2019
DOI: 10.1002/ccd.28333
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transaxillary approach for peripheral endovascular interventions

Abstract: Objectives To assess the safety and feasibility of percutaneous transaxillary (TAx) access for peripheral endovascular interventions. Background The common femoral artery (CFA) is the most commonly used access site for peripheral endovascular interventions. However, its use might be precluded in multiple circumstances. The axillary artery is comparable in size to the CFA and is less affected by atherosclerosis. Data regarding its percutaneous use in peripheral endovascular interventions are scarce. Methods Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In this study, the femoral and brachial approaches were performed in 17 patients, the majority of whom TASC C & D lesions, with a technical success rate of approximately 94.1%. Thawabi et al ( 12 ) reported a high technical success rate (97.5%, 40/41) in the transaxillary approach for patients with unsuitable femoral access; however, there was a 5% puncture-site-related complication rate. Millon et al ( 6 ) reported only the brachial approach, with a 93% technical success rate for extensive AIOD involving distal aortic occlusion ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the femoral and brachial approaches were performed in 17 patients, the majority of whom TASC C & D lesions, with a technical success rate of approximately 94.1%. Thawabi et al ( 12 ) reported a high technical success rate (97.5%, 40/41) in the transaxillary approach for patients with unsuitable femoral access; however, there was a 5% puncture-site-related complication rate. Millon et al ( 6 ) reported only the brachial approach, with a 93% technical success rate for extensive AIOD involving distal aortic occlusion ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous axillary access has been shown to be a reasonable alternative to brachial access for endovascular therapy of complex aortoiliac disease 1 given the high complication rate of the latter 2 and the better anatomical suitability for percutaneous axillary closure and bailout stenting. 3,4 A shallow angle of axillary needle entry is key 5 ; however, a longer than 7 cm micropuncture needle was not available here.…”
Section: Discussionmentioning
confidence: 99%